(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
In this article, through a survey, the activities of farms specializing in growing fruits and vegetables in the Surkhandarya region were studied, and it was found that farms have problems using loans. In addition, proposals and conclusions were formulated to solve problems and support the activities of farms.